Optimal Reconfiguration of Radial Distribution Systems Using a Fuzzy Mutated Genetic Algorithm - Prasad, K.; Ranjan, R.; Sahoo, N.C.; Chaturvedi, A. (2005)
A new method based on a fuzzy mutated genetic algorithm for optimal reconfiguration of radial distribution systems (RDS) is presented. The proposed algorithm overcomes the combinatorial nature of the reconfiguration problem and deals with noncontinuous multi-objective optimization. The attractive features of the algorithm are: preservation of radial property of the network without islanding any load point by an elegant coding scheme and an efficient convergence characteristic attributed to a controlled mutation using fuzzy logic.